Trigeminal Neuralgia Due to Red Vein Draining a Supratentorial Arteriovenous Malformation: Case Report - Inoue, Takuro; Shima, Ayako; Hirai, Hisao; Suzuki, Fumio; Matsuda, Masayuki (Journal of Neurological Surgery Reports, 2016)
Trigeminal neuralgia (TGN) is rarely caused by arteriovenous malformation (AVM). The AVMs causing TGN are reported mostly in the ipsilateral posterior fossa. The culprit vessels are dilated feeding artery or nidus itself. We present a rare case of TGN caused by dilated draining veins from a supratentorial AVM. The patient suffered from TGN with an incidentally found large AVM, which had been left untreated. The neuralgia was successfully relieved by microvascular decompression. Dilated red veins compressed the nerve at the root entry zone and distant cisternal portion of the nerve. Technically, transposition is not practical for fragile, dilated red veins with high pressure. Interposition is safer method in this case.
Keywords: arteriovenous malformation; trigeminal neuralgia; vein; microvascular decompression